Developing metacognitive awareness through Duolingo application in enhancing students' self-reliance in learning speaking - Budiono, Agustinus Dheny; Senowarsito, Senowarsito; Susanto, Dias Andris (EduLite: Journal of English Education, Literature and Culture, 2025)
English Learners need to develop a willingness to learn independently. Due to this challenge, it is essential to foster students' metacognitive awareness, comprising the ability to understand, control, and manage the own learning process. The Duolingo application holds a potential to enhance students' metacognitive awareness, so far not much research has investigated this focus. Therefore, this research aims at investigating the role of Duolingo in developing students’ metacognitive awareness in learning to speak English; examining differences in students’ level of metacognitive awareness; and describing how the Duolingo fosters the students’ self-reliance in learning to speak English. The research involved 70 high school students in Semarang City and employed a Concurrent Nested Design. This research focused on measuring changes in the level of metacognitive awareness of the students before and after using Duolingo. Data collected from interview were used to describe how students used the application to improve their learning independence. The results revealed a significant improvement in students’ metacognitive awareness, with the mean pre-test score increasing from 79.43 to 91.81—a gain of 12.38 points. The standard deviation decreased from 6.606 (pre-test) to 5.483 (post-test), and the average N-gain score was 0.64, indicating a 64% mean percentage improvement. Although most participants improved significantly, there was notable variation in the improvement. Qualitative findings highlighted diverse perceptions and approaches among students, emphasizing Duolingo’s effectiveness in promoting independent learning and enhancing metacognitive awareness. This study underscores the value of integrating technology into language learning to support self-directed learning and metacognitive skill development.